2015
DOI: 10.1016/j.ecolecon.2015.09.021
|View full text |Cite
|
Sign up to set email alerts
|

National well-being policy and a weighted approach to human feelings

Abstract: Governments are becoming interested in the concept of human well-being and how truly to assess it. As an alternative to traditional economic measures, some nations have begun to collect information on citizens’ happiness, life satisfaction, and other psychological scores. Yet how could such data actually be used? This paper is a cautious attempt to contribute to thinking on that question. It suggests a possible weighting method to calculate first-order changes in society’s well-being, discusses some of the pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 141 publications
0
19
0
Order By: Relevance
“…Rather than just the absence of mental illness, mental wellbeing therefore encompasses aspects of positive affect, relaxation, functioning, personal relationships, life satisfaction and general happiness [17–19]. …”
Section: Introductionmentioning
confidence: 99%
“…Rather than just the absence of mental illness, mental wellbeing therefore encompasses aspects of positive affect, relaxation, functioning, personal relationships, life satisfaction and general happiness [17–19]. …”
Section: Introductionmentioning
confidence: 99%
“…McLaughlin ), people in the 20th century gained negative freedom (freedom from the pressure of entrenched cultural norms), without winning positive freedom (freedom to do something meaningful and fulfilling with their newly acquired liberty). This explanatory framework, although not as powerful as it used to be in the 1960s and the 1970s, still makes it possible to account for the apparent paradox that the frequency of depression and suicide in advanced capitalist societies has increased despite the parallel increase in material wealth (Layard ; Hidaka ; O'Donnell and Oswald ; Balayannis and Cook ). More recent research on meaning (Wegner and Gray ; King et al .…”
Section: Hedonism Virtue and Meaning‐makingmentioning
confidence: 99%
“…3 In recent years, subjective well-being measures, such as happiness and life satisfaction measured with large representative surveys, have become increasingly popular in this regard and some authors (e.g. Layard, 2005, O'Donnell andOswald, 2015) have advocated the use of these indicators in policy evaluation. Numerous studies have indeed shown that non-monetary life dimensions, in addition to income, are important determinants of subjective well-being.…”
Section: Subjective Well-beingmentioning
confidence: 99%